2021
DOI: 10.1177/10775595211034763
|View full text |Cite
|
Sign up to set email alerts
|

Connected After Care: Youth Characteristics, Policy, and Programs Associated With Postsecondary Education and Employment for Youth With Foster Care Histories

Abstract: Recent federal laws and state policies reflect the government’s investment in improving education and employment outcomes for youth with foster care histories. However, little research has assessed the roles of these programs using national data. Drawing on data from the National Youth in Transitions Database (NYTD) ( n = 7797), this study examines the roles that state-level policies and programs, youth-level participation in programs and services, and youth characteristics play in youths’ connection to employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Very few research studies in our field focus specifically on the experiences of Black, Latinx, and Indigenous students with experience in foster care, despite the data that tells us these populations are overrepresented in the foster care system. Data disaggregation is standard in both the fields of social work and education, however, with a few notable exceptions (i.e., Geiger & Okpych, 2022), there is a distinct lack of disaggregated data related to our students of color with experience in foster care. We must insist that this basic data and research principle becomes standard practice in our field, regardless of the naysayers who push back by excusing the population as too small.…”
Section: The Subtle Ways We Fail Our Studentsmentioning
confidence: 99%
“…Very few research studies in our field focus specifically on the experiences of Black, Latinx, and Indigenous students with experience in foster care, despite the data that tells us these populations are overrepresented in the foster care system. Data disaggregation is standard in both the fields of social work and education, however, with a few notable exceptions (i.e., Geiger & Okpych, 2022), there is a distinct lack of disaggregated data related to our students of color with experience in foster care. We must insist that this basic data and research principle becomes standard practice in our field, regardless of the naysayers who push back by excusing the population as too small.…”
Section: The Subtle Ways We Fail Our Studentsmentioning
confidence: 99%
“…Several studies have controlled for giving birth or fathering a child in multivariate models predicting postsecondary educational attainment among young people currently or formerly in foster care (e.g., Courtney & Hook, 2017;Geiger & Okpych, 2021;Okpych, 2021;Salazar et al, 2019).…”
Section: Early Childbirth and Access To Postsecondary Educationmentioning
confidence: 99%
“…Several studies have controlled for giving birth or fathering a child in multivariate models predicting postsecondary educational attainment among young people currently or formerly in foster care (e.g., Courtney & Hook, 2017; Geiger & Okpych, 2021; Okpych, 2021; Okpych & Courtney, 2017; Okpych et al, 2017; Salazar et al, 2019). However, the main focus of these studies was not on the effects of parenthood on access to postsecondary education.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty-two percent of children in foster care identify as Hispanic 1 (U.S. Department of Health and Human Services, 2021). Research findings are mixed, with some studies showing Hispanic youth were more likely to be enrolled in college (Geiger & Okpych, 2022;Rosenberg & Kim, 2018;Watt & Kim, 2019), while another study found no significant differences (Okpych & Courtney, 2017). Select studies have examined gender, racial, and ethnic differences and/or disparities among youth with foster care histories as it relates to educational outcomes (e.g., Dworsky et al, 2010;Harris et al, 2009;Kirk et al, 2012); however, few have explored how components of ethnoracial identity play a role in their experiences (Lane, 2016(Lane, , 2017Tyrell et al, 2019) or how multiple marginalized identities intersect to shape the college experiences of students with a foster care background.…”
mentioning
confidence: 99%